Effect of micro-irrigation on water productivity in system of rice (Oryza sativa) and wheat (Triticum aestivum) intensification - KUMAR, AJAY; SINGH, S K; KAUSHAL, K K; PURUSHOTTAM, PURUSHOTTAM (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during 2011-2013 to study the performance of different irrigation methods on water productivity in system of rice and wheat intensification (SRI and SWI) at research farm of ICAR-Research Complex for Eastern Region, Patna. Three methods of irrigation, Low Energy Water Application (LEWA), microsprinkler and check basin irrigation methods were combined with three establishment methods SRI/SWI, line transplanting/sowing and farmers’ practices of transplanting/sowing respectively, in rice (Oryza sativa L.) and wheat (Triticum aestivum L.) crops laid out in 32 factorial randomized block design. SRI under micro irrigation system (LEWA and micro-sprinkler) resulted in significantly higher (128 and 123 %) grain yield of rice as compared to farmersâ€™ practice of rice transplanting under check basin irrigation (3.80 tonnes/ha). However, the grain yield variation between LEWA and micro-sprinkler irrigation under different establishment methods was insignificant. Whereas, a combination of SRI and micro-irrigation (LEWA and micro-sprinkler) significantly increased water productivity by 153 and 156 % respectively in comparison to check basin under framers’ practices of rice establishment (0.34 kg/m3). There was a mean saving of 27 and 39% water observed in LEWA and micro sprinkler irrigation, respectively as compared to check basin irrigation (340 mm) in rice crop. In case of wheat, SWI in combination with micro-irrigation system (LEWA and micro-sprinkler) recorded significantly higher (132 and 131%) grain yield in comparison to farmers’ practice of wheat establishment under check basin irrigation (3.10 tonne/ha). Whereas, a combination of SWI and micro-irrigation (LEWA and micro-sprinkler) significantly increased water productivity by 190 and 233 % respectively in comparison to check basin under framers’ practices of wheat establishments (1.07 kg/m3). There was a mean saving of 23 and 36% water observed in LEWA and micro-sprinkler irrigation respectively as compared to check basin irrigation (249 mm) in wheat crop. It has been clearly established that SRI and SWI in combination with micro-irrigation played crucial role in enhancing the grain yield and water productivity of rice and wheat.